Changes in Neuroendovascular Procedural Volume During the COVID‐19 Pandemic: An International Multicenter Study. Issue 1 (23rd November 2020) - Qureshi, Adnan I.; Agunbiade, Samiat; Huang, Wei; Akhtar, Iqra N.; Abraham, Michael G.; Akhtar, Naveed; Al‐Mufti, Fawaz; Aytac, Emrah; Balgetir, Ferhat; Grigoryan, Mikayel; Gomez, Camilo R.; Hassan, Ameer E.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: The effect of coronavirus disease 2019 (COVID‐19) pandemic on performance of neuroendovascular procedures has not been quantified. METHODS: We performed an audit of performance of neuroendovascular procedures at 18 institutions (seven countries) for two periods; January‐April 2019 and 2020, to identify changes in various core procedures. We divided the region where the hospital was located based on the median value of total number of COVID‐19 cases per 100, 00 population‐into high and low prevalent regions. RESULTS: Between 2019 and 2020, there was a reduction in number of cerebral angiograms (30.9% reduction), mechanical thrombectomy (8% reduction), carotid artery stent placement for symptomatic (22.7% reduction) and asymptomatic (43.4% reduction) stenoses, intracranial angioplasty and/or stent placement (45% reduction), and endovascular treatment of unruptured intracranial aneurysms (44.6% reduction) and ruptured (22.9% reduction) and unruptured brain arteriovenous malformations (66.4% reduction). There was an increase in the treatment of ruptured intracranial aneurysms (10% increase) and other neuroendovascular procedures (34.9% increase). There was no relationship between procedural volume change and intuitional location in high or low COVID‐19 prevalent regions. The procedural volume reduction was mainly observed in March‐April 2020. CONCLUSIONS: We provided an international multicenter view of changes in neuroendovascular practices to better understand the gaps in provision of care and identify individual procedures, which are susceptible to change.